2022
DOI: 10.1039/d1tc04877e
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic wetting enabled high resolution liquid metal patterning for 3D and flexible electronics

Abstract: Liquid metals, highly conductive and flowable metals, are increasingly becoming versatile choices for soft electronics and wearable devices. High resolution liquid metal patterning strategies accommodative to different substrate materials and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…2 c. In this work, the size limitation is 0.3 mm due to the resolution of laser engraving and high surface tension of the LM. However, the size limitation for electronics printing can be further improved with the advanced laser fabrication or other lithographic method [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 c. In this work, the size limitation is 0.3 mm due to the resolution of laser engraving and high surface tension of the LM. However, the size limitation for electronics printing can be further improved with the advanced laser fabrication or other lithographic method [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…S2. Generally, the adhesion ability can be used to measure the attraction between liquid and solid or required energy of separate interface reversibly [ 29 ], and the work of adhesion of LM to a solid surface W SL can be calculated by the Young-Dupre equation as the following where W SL is the work of adhesion between solid–liquid interface, σ LG is the surface tension of the liquid–gas interface, θ is the contact angle. It can be concluded that larger surface tension and a smaller value of contact angle will produce a stronger work of adhesion, which lead to a better performance in the adhesion and wetting abilities of the liquid (LM) to a solid surface (substrates).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it always needs extremely complex, high‐cost, and repetitive electron‐beam/optical lithography in these reports. [ 27,43–44 ] This is because these reported active metals (e.g., Cu/Ni/Fe/Ag) for LMs’ plating usually exhibit weak adhesion to the elastic substrates (e.g., poly(dimethylsiloxane), polyurethane). When LMs were directly deposited onto these metals, they would be easily corrupted or dissolved by LMs due to the high alloying interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The room-temperature liquid metal (LM, gallium alloys) has been widely concerned due to its low-temperature melting point, high thermal and electrical conductivities, and non-toxicity [ 7 , 8 ]. LM has been widely applied to biomedical technology [ 9 , 10 ], flexible electronics [ 11 , 12 , 13 ], soft machines [ 14 , 15 ], high heat-flux thermal management [ 16 , 17 , 18 , 19 ], and energy harvesting [ 20 ]. The gallium-based LM has been also used as stretchable electrodes to WTEG due to its excellent fluidity [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%